2011
DOI: 10.3109/07853890.2010.546362
|View full text |Cite
|
Sign up to set email alerts
|

The CD40-CD40L system in cardiovascular disease

Abstract: The CD40-CD40L system is a pathway which is associated with both prothrombotic and proinflammatory effects. CD40 and its ligand were first discovered on the surface of activated T cells, but its presence on B cells, antigen-presenting cells, mast cells, and finally platelets, is evident. The soluble form of CD40L (sCD40L) is derived mainly from activated platelets and contributes to the pathophysiology of atherosclerosis and atherothrombosis. Indeed, sCD40L has autocrine, paracrine, and endocrine activities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 88 publications
1
89
1
3
Order By: Relevance
“…They are gaining increasing attention in the field of tumor immunology (6)(7)(8). It has been reported that CD40-CD40L axis was involved in a series of cell biological activities, such as cancer, cardiovascular disease, immune disorders, and even Alzheimer's disease (9)(10)(11). CD40 was found to be expressed at an up-regulated level in many epithelial cancers (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…They are gaining increasing attention in the field of tumor immunology (6)(7)(8). It has been reported that CD40-CD40L axis was involved in a series of cell biological activities, such as cancer, cardiovascular disease, immune disorders, and even Alzheimer's disease (9)(10)(11). CD40 was found to be expressed at an up-regulated level in many epithelial cancers (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism H6D in GDF15 has not previously been shown to be important for CVD events, but serum levels of GDF15 were related to CVD in the general population 27,28 and in patients with RA 30 . Both CD40 and GDF15/MIC-1 have immunoregulatory properties 25,31,38 . In the patients with RA, we were able to confirm associations with these selected SNP and CVD.…”
Section: Rheumatologymentioning
confidence: 99%
“…74 Most circulating CD40L is expressed in platelets, which are not only critical elements for homeostasis, but also have the potential to trigger an inflammatory response in the vascular wall. 75 Once activated, platelets promptly express CD40L, which, in turn, induces endothelial cells to secrete chemokines and to express adhesion molecules, thereby promoting the recruitment and extravasation of leukocytes at the site of injury.…”
Section: Cd40 Ligand (Cd40l)mentioning
confidence: 99%